Nano Zero-Valent Iron Mediated Metal(loid) Uptake and Translocation by Arbuscular Mycorrhizal Symbioses - Wu, Songlin; Vosátka, Miroslav; Vogel-Mikus, Katarina; Kavčič, Anja; Kelemen, Mitja; Šepec, Luka; Pelicon, Primož; Skála, Roman; Valero Powter, Antonio Roberto; Teodoro, Manuel; Michálková, Zuzana; Komárek, Michael (Environmental science & technology, 2018)
Nano zero-valent iron (nZVI) has great potential in the remediation of metal(loid)-contaminated soils, but its efficiency in metal(loid) stabilization in the plant-microbe continuum is unclear. This study investigated nZVI-mediated metal(loid) behavior in the arbuscular mycorrhizal (AM) fungal-maize ( Zea mays L.) plant association. Plants with AM fungal inoculation were grown in metal(loid)- (mainly Zn and Pb) contaminated soils (Litavka River, Czech Republic) amended with/without 0.5% (w/w) nZVI. The results showed that nZVI decreased plant metal(loid) uptake but inhibited AM development and its function in metal(loid) stabilization in the rhizosphere. AM fungal inoculation alleviated the physiological stresses caused by nZVI and restrained nZVI efficiency in reducing plant metal(loid) uptake. Micro proton-induced X-ray emission (μ-PIXE) analysis revealed the sequestration of Zn (possibly through binding to thiols) by fungal structures in the roots and the precipitation of Pb and Cu in the mycorrhizal root rhizodermis (possibly by Fe compounds originated from nZVI). XRD analyses further indicated that Pb/Fe mineral transformations in the rhizosphere were influenced by AM and nZVI treatments. The study revealed the counteractive effects of AM and nZVI on plant metal(loid) uptake and uncovered details of metal(loid) behavior in the AM fungal-root-nZVI system, calling into question about nZVI implementation in mycorrhizospheric systems.
Keywords: mykorhiza; Česká republika; látky znečišťující půdu; Mycorrhizae; Plant Roots; kořeny rostlin; těžké kovy; Iron; Metals, Heavy; Czech Republic; železo; Soil Pollutants